PENGARUH ROTASI KERJA DAN PENDIDIKAN BERKELANJUTAN DALAM PENGEMBANGAN SDM TERHADAP KINERJA KARYAWAN PADA SALAH SATU PERUSAHAAN DI KAWASAN INDUSTRI KOTA MAKASSAR - Safrin D Talli, Abdul; Sulaiman, Sulaiman (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
Improving efficiency and effectiveness of employee performance can be achieved through job rotation practices, as human resources represent valuable organizational assets that must be managed optimally to maximize their contribution. Employees are encouraged to proactively enhance their competencies, which can be facilitated through human resource development programs, particularly continuing education. This study aims to examine the influence of job rotation and continuing education in human resource development on employee performance at one of the companies located in the Makassar City Industrial Area. Data were collected through questionnaire distribution to 86 respondents selected using a simple random sampling technique. Prior to analysis, data quality tests were conducted, followed by multiple regression analysis, partial testing, and coefficient of determination analysis. The findings reveal that job rotation and continuing education, both partially and simultaneously, have a positive and significant effect on employee performance. Among the two variables, job rotation demonstrates a more dominant contribution, motivating employees to improve their performance and pursue higher career advancement.